Design and development of novel single multiplex system incorporating 26 rapidly mutating Y‐STRs; 26 RM Yplex. Issue 18 (8th August 2022) - Albastaki, Abdulla; Naji, Mohammed; Lootah, Reem; Almheiri, Reem; Almulla, Hanan; Alreyami, Afra; Almarri, Iman; Yu, Zailiang; Zhang, Yueke; Shu, Chang; Alghafri, Rashed
Abstract: This article details the development of a single multiplex system amplifying 26 rapidly mutating Y‐STR markers. A sequenced allelic ladder, constructed for calling alleles of all loci, is introduced. The multiplex system shows the ability to address the limitations of Y‐STRs commercial kits in differentiating closely related males. The multiplex performed well in the prevalidation tests and showed great potential to be used in forensic casework.